Traces of Islamic Astronomy and the Residue of Sufism in Determining The Beginning of Ramadan on the Maluku Muslim Community - Kalean, Arman (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2024)
The Wandering Sufi have given their own traces of Islam in the archipelago, namely the traces of Sufism and also the traces of Islamic Astronomy. This Wandering Sufi has been present in the archipelago since the early days of Islamic trade, including in Maluku. The existence of several customs in Islamic rituals in several areas in Maluku, authentically confirms the Islamic style embraced by the Maluku people. This study found that there is a trace of Islamic astronomy in Maluku, in the form of a calendar concept that has a display pattern similar to the Javanese and Sumatran Islamic calendars, and has an Arabic numerological concept with beliefs similar to those in the Banjar Society. In addition, this study also provides an overview of the residue of Sufism teachings in the form of the Qadiriyah and Shattariyah orders.